2022
DOI: 10.3389/fmicb.2022.872735
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Versus Frozen Stool for Fecal Microbiota Transplantation—Assessment by Multimethod Approach Combining Culturing, Flow Cytometry, and Next-Generation Sequencing

Abstract: The objective of this work was to compare the quality of FMT preparations made from fresh feces with those made from feces frozen at –30°C without any pre-processing or cryopreservation additives. The research hypothesis was that such preservation protocol (frozen whole stool, then thawed and processed) is equipotent to classical fresh FMT preparation. For that, three complementary methods were applied, including: (i) culturing in aerobic and anaerobic conditions, (ii) measuring viability by flow cytometry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We used stool from germ-free (GF) mice, devoid of bacteria, to establish a noise threshold and compared this with stool from conventionally bred (CONV) mice, containing both bacterial and non-bacterial elements (Figure 4). This approach allowed us to define four viability quadrants based on SYTO9 and PI fluorescence, categorizing cells as dead, dying or damaged, viable, or of unknown status (20,21). We observed significantly fewer fluorescent events in GF mouse stool, attributing this to non-bacterial autofluorescence or staining artifacts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used stool from germ-free (GF) mice, devoid of bacteria, to establish a noise threshold and compared this with stool from conventionally bred (CONV) mice, containing both bacterial and non-bacterial elements (Figure 4). This approach allowed us to define four viability quadrants based on SYTO9 and PI fluorescence, categorizing cells as dead, dying or damaged, viable, or of unknown status (20,21). We observed significantly fewer fluorescent events in GF mouse stool, attributing this to non-bacterial autofluorescence or staining artifacts.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent staining for membrane integrity, typically performed with flow cytometry, is a commonly adopted culture-independent method (35)(36)(37). Nevertheless, its effectiveness can vary across different bacterial taxa, and its application to the heterogeneous matrix of stool presents additional challenges (20,21,29,32) Given these complexities, we compared the two prevalent methods-cultivation and membrane integrity assessment-for their accuracy and clinical applicability. Our adaptation of the LIVE/DEAD™ BacLight™ Bacterial Viability Kit for stool analysis demonstrated the potential to discriminate between microbial DNA signals and background noise effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several issues of the current study could be better addressed in future investigations. A recent report highlights alterations in stool microbiome upon sample freezing without the addition of cryoprotectants (Bilinski et al, 2022). In our analysis, we only report data from both fresh and frozen stool samples, and do not account for potential changes caused by cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, freezing of feces is known to impact microbiome composition. It leads to a 4-fold reduction in living bacterial cells as detected by flow cytometry (70% to 15%), similar alpha diversity, and definite differences in beta diversity on principal coordinates analysis from fresh fecal samples [ 53 ]. Prolonged frozen storage leads to an increase in Firmicutes to Bacteroidetes ratio, as some Gram-negative species are depleted during storage and some hypothesize that trials in which frozen FMT was found to be effective also depend on this phenomena of selective depletion of administered Bacteroidetes .…”
Section: Procedure-related Factors and Outcome Determinants In Fmtmentioning
confidence: 99%